Camellia neriifolia and Camellia ilicifolia (Theaceae) as separate species: evidence from morphology, anatomy, palynology, molecular systematics - Ran, Zhaohui; Li, Zhi; Xiao, Xu; Tang, Ming (Botanical studies, 2024)
Background The systematic status of sect. Tuberculata and its taxonomy have recently attracted considerable attention. However, the different bases for defining the characteristics of sect. Tuberculata has led to many disagreements among the plants in this group. Camellia neriifolia and Camellia ilicifolia have been the subject of taxonomic controversy and have been treated as different species or varieties of the same species. Therefore, it is important to use multiple methods, i.e., integrative taxonomy, to determine the taxonomic status of C. neriifoli a and C. ilicifolia . This is the first study to systematically explore the taxonomic position of these two plants on the basis of Morphology, Anatomy, Palynology and Molecular Systematics. Results Extensive specimen reviews and field surveys showed that many differences exist in C. neriifolia and C. ilicifolia , such as the number of trunk (heavily debarked vs. slightly peeling), leaf type (smooth thin leathery, shiny vs. smooth leathery, obscure or slightly shiny), leaf margin (entire vs. serrate), flower type (subsessile vs. sessile), number of styles (3–4 vs. 3), and sepal (ovate vs. round). Moreover, C. neriifolia has a more distinctive faint yellow flower color, and trunk molting was more severe in C. neriifolia than that in C. ilicifolia . In addition, micromorphological analysis of the leaf epidermis showed that the two species differed in the anticlinal wall, stomatal apparatus, and stomatal cluster, and pollen morphology analyses based on pollen size, germination furrow, and polar and equatorial axes showed that they are both distinct from each other. The results of the phylogenetic tree constructed based on the whole chloroplast genome, protein-coding genes, and ITS2 showed that both C. ilicifolia and C. neriifolia were clustered in different branches and gained high support. Conclusions The results combine morphology, anatomy, palynology, and molecular systematics to treat both C. neriifolia and C. ilicifolia as separate species in the sect. Tuberculata , and the species names continue to be used as they were previously. In conclusion, clarifying the taxonomic status of C. neriifolia and C. ilicifolia deepens our understanding of the systematic classification of sect. Tuberculata .